Fiscal Policy Behaviour in ASEAN: Countercyclical or Procyclical? - Fitriaini, Raisa (KnE Social Sciences, 2020)
Fiscal policy is a policy imposed by the government to influence economic activity in the real sector through expenditure and revenue. Fiscal policy help in smoothing business cycle fluctuations (boom or recession) makes it a potential tool for economic stabilization. Referring to the theory, fiscal policy should have a countercyclical behaviour. Vice versa, many evidence shows if the behaviour of fiscal policy diverse among countries. Therefore, the purpose of this study is to find the fiscal policy behaviour in ASEAN (2001-2018) using the Panel Least Square analysis tool. The estimation results show that the behaviour of fiscal policy in ASEAN are countercyclical for government revenue approach and fiscal balance approach, whereas government expenditure approach is procyclical. Keywords: fiscal policy, fiscal policy behaviour, countercyclical, procyclical